Distribution of Skipjack (Katsuwonus Pelamis) Fishing Areas using Purse Seine Fishing Equipment in WPP 573: Distribusi Daerah Penangkapan Ikan Cakalang (Katsuwonus pelamis) Menggunakan Alat Tangkap Purse Seine di WPP 573 - Muhammad Nursan; Yonvitner Yonvitner; Syamsul Bahri Agus (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2022)
Estimation of fishing grounds is one solution to facilitate time efficiency in fishing activities. Efforts are made to predict the fishing ground (fishing ground) through an approach to oceanographic physical conditions. The dynamics of skipjack fishing areas are influenced by oceanographic parameters such as sea surface temperature and chlorophyll-a concentration. Skipjack tuna (Katsuwonus pelamis) is the main type of fish caught in Indonesian waters. This study aims to analyze the dynamics of oceanographic conditions in the form of sea surface temperature and chlorophyll-a distribution, the relationship between skipjack fishing season and the dynamics of sea surface temperature distribution and chlorophyll-a distribution in WPP 573 waters 2016-2020 and predict skipjack fishing season.The catch results show that the average SST value obtained from the fishing grounds is 29.44 oC, the minimum value is 26.76 oC and the maximum value is 32.32 oC, while for the concentration of chlorophyll-a the average value obtained is 0.19 mg/ m3, the minimum value is 0.08 mg/m3 and the maximum value is 0.95 mg/m3. The average temperature and chlorophyll-a 2016-2020 that coincided with the high catch were 28.5oC and 0.23 mg/m3. The results of the MaxEnt model show that the evaluation of the model is in a good category, the percentage of SST contribution is higher than Chlorophyll-a, the probability index value for skipjack fish is around 0.5-0.8 and the results of the validation of fishing data are mostly widespread according to the results of the 2016-2020 MaxEnt model. The results also show that the east season, namely June, July and August, is a good fishing season for skipjack tuna, whereas skipjack catches decline in the west season, December, January and February.